Social Stigma of COVID-19: A Semiotic Analysis of WHO Campaign Posters - Intan Siti Nugraha; Azka Saeful Haq (Soshum: Jurnal Sosial dan Humaniora, 2021)
COVID-19 has been reported to be risen in numbers of infected cases and deaths. The massive report by media and social network which focus on the spreading and infection may affect not only physical health but also individual’s and general population’s mental health, isolation and stigma. To eradicate COVID-19-related stigma and discrimination perpetuated by both individual and group of people, WHO exhibits some anti-stigma campaign posters. This study employs qualitative method to acquire deep investigation of meaning and to involve the social context. Thus, by using Roland Barthes’s semiotic approach, analyzing signifiers and signifieds, this study was aimed to unmask both denotative and connotative meanings of the stigma embed within the six health campaign posters of COVID-19 by Southeast Asia WHO. The analysis was focused not only on the verbal sign of posters (linguistic text), but also its relation to their visual sign (imagery messages). From the analysis of the two sign systems of posters, the result shows that the six posters connote acts of discriminatory behaviours, stigmatization, stereotype and blaming. Through the posters, WHO propagates people to work together to fight COVID-19 and to bring out the best humanity, to have better awareness and positive attitudes and appeals governments, citizens, media, key influencers of communities to have a role in preventing and to stop stigma surrounding in South-Asia and specifically in Indonesia which becomes the target of the poster viewers during the pandemic. Those messages are connoted through different font colors and sizes and the illustration on each poster.